2016
DOI: 10.1002/etc.3200
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium potentiates toxicity of cypermethrin in zebrafish

Abstract: Co-occurrence of pesticides such as synthetic pyrethroids and metals in aquatic ecosystems raises concerns over their combined ecological effects. Cypermethrin, 1 of the top 5 synthetic pyrethroids in use, has been extensively detected in surface water. Cadmium (Cd) has been recognized as 1 of the most toxic metals and is a common contaminant in the aquatic system. However, little information is available regarding their joint toxicity. In the present study, combined toxicity of cypermethrin and Cd and the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 53 publications
(77 reference statements)
2
24
0
1
Order By: Relevance
“…In agreement with this observation, our recent study showed that Cd inhibited CYP-catalyzed biodegradation of CP in zebrafish [27]. In agreement with this observation, our recent study showed that Cd inhibited CYP-catalyzed biodegradation of CP in zebrafish [27].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In agreement with this observation, our recent study showed that Cd inhibited CYP-catalyzed biodegradation of CP in zebrafish [27]. In agreement with this observation, our recent study showed that Cd inhibited CYP-catalyzed biodegradation of CP in zebrafish [27].…”
Section: Discussionsupporting
confidence: 87%
“…The animals were maintained in the laboratory at optimal conditions for at least 1 wk before exposure experiments, according to the well-established protocols previously described [27]. The animals were maintained in the laboratory at optimal conditions for at least 1 wk before exposure experiments, according to the well-established protocols previously described [27].…”
Section: Experimental Animalsmentioning
confidence: 99%
See 3 more Smart Citations